Cardiac conduction abnormalities in patients with degenerated bioprostheses undergoing transcatheter aortic valve-in-valve implantations and their impact on long-term outcomes. (1st May 2021) - Stankowski, Tomasz; Mangner, Norman; Linke, Axel; Aboul-Hassan, Sleiman Sebastian; Gąsior, Tomasz; Muehle, Anja; Herwig, Volker; Harnath, Axel; Salem, Mohammed; Szłapka, Michał; Grimmig, Oliver; Just, Soeren; et al.
Abstract: Background: The relationship between preoperative cardiac conduction abnormalities (CCA) and long-term outcomes after transcatheter aortic valve-in-valve implantation (TAVI-VIV) remains unclear. The aim of the study was to evaluate the effects of preoperative CCA on mortality and morbidity after TAVI-VIV and to estimate the impact of new-onset CCA on postoperative outcomes. Methods: Between 2011 and 2020, 201 patients with degenerated aortic bioprostheses were qualified for TAVI-VIV procedures in two German heart centers. Cases with previously implanted permanent rhythm-controlling devices were excluded ( n = 53). A total of 148 subjects met the eligibility criteria and were divided into 2 study groups according to the presence of preexisting CCA (CCA ( n = 84) and non-CCA ( n = 64), respectively). Early and late mortality and morbidity were evaluated. Follow-up functional status was assessed according to New York Heart Association (NYHA) classification. Results: There were no procedural deaths. TAVI-VIV related new-onset CCAs were observed in 35.8% patients. The 30-day permanent pacemaker implantation rate was 1.6% in non-CCA vs 9.5% in CCA group ( p = 0.045). Preexisting right bundle-branch block (OR:5.01; 95%CI, 1.05–23.84) and first-degree atrioventricular block (OR:4.55; 95%CI, 1.10–18.73) were independent predictors of new pacemaker implantation. One-year and five-year probability of survival were comparable in CCA and non-CCA groups: 90.3% vs 91.8% and 68.2% vs 74.3%, respectively. Surviving patients with preexisting and new-onset CCA had a worse functional status according to NYHA classification at follow-up. Conclusion: Preexisting and new-onset postoperative CCAs did not affect early and late mortality after TAVI-VIV procedures, however, they may have a negative impact on late functional status. Highlights: Every second patient qualified for TAVI-VIV has preexisting CCA. Preexisting and new-onset postoperative CCAs did not affect mortality after TAVI-VIV. Preexisting and new-onset postoperative CCAs affect negatively on NYHA class and LV EF after TAVI-VIV. Preexisting CCA leads to a higher rate of 30-day pacemaker implantation after TAVI-VIV. RBBB and AVB I are risk factors for new pacemaker implantation following TAVI-VIV.